The Aesthetics of Digital Montage : Film Editing and Technological Change - Furstenau, Marc (Amsterdam : Amsterdam University Press, 2024)
Tracing the recent changes to the technology of film editing, this book offers an account of the aesthetics of digital montage. It is commonly argued that the changes to the technical apparatus of editing, the emergence of new systems for digital editing, have altered the basic identity or ontology of the cinema as an art. Such claims, it is argued in this book, are based on a misunderstanding of the relation between technology and technique, and more generally between the technical and the aesthetic. Applying recent theories of art, and employing specific concepts from philosophical aesthetics, an account of cinematic art is offered that can better accommodate the kinds of technical changes that have occurred in recent decades, with the advent of computer technology in the cinema. An aesthetics of digital montage is presented as part of a more general proposal for a theory of technical change in the cinema.
Frontmatter -- Table of Contents -- List of Illustrations -- Introduction -- 1. The Fate of Film Editing -- 2. Editing, Intention, and the Work of Film Art -- 3. The Technology and Technique of Film Editing -- 4. Digital Montage and the Ontology of the Cinema -- 5. The Art of Editing in the Digital Era -- Conclusion -- Acknowledgements -- Bibliography -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 17, 2024).
JSTOR
Keywords: Motion pictures -- Editing; Digital cinematography; Montage (Cinéma); Cinéma numérique.; ART / Digital; Electronic books; Electronic books